SIKAP KERJA SISWA PROGRAM STUDI KONSTRUKSI KAYU JURUSAN BANGUNAN SMK N 1 PADANG SETELAH MELAKSANAKAN PRAKERIN - 190-194 , Afria Ulfa (Universitas Negeri Padang, 2013)
This research is purposed to find out student’s work attitudes for timber construction subject in construction major class SMKN 1 Padang, year of school 2012/2013. Problem that being identified in this research is the lack of employment for students of SMK; this is proved that they should have not only skills but also positive work attitudes. This research is descriptive. Population in this research is 16 students of construction major class XI SMKN 1 Padang, year of school 2012/2013, that performed apprenticeship. Instrument that used for data collection is questionnaire, while data analysis technique that being used in this research is statistical descriptive with percentage computation. Based on results found out that for student’s attitudes for timber construction subject is good with percentage is 80.89%. Key words : attitudes work, prakerin, praktek kerja kayu.